2020
DOI: 10.2196/23241
|View full text |Cite
|
Sign up to set email alerts
|

Harmonized One Health Trans-Species and Community Surveillance for Tackling Antibacterial Resistance in India: Protocol for a Mixed Methods Study

Abstract: Background India has the largest burden of drug‑resistant organisms compared with other countries around the world, including multiresistant and extremely drug‑resistant tuberculosis and resistant Gram‑negative and Gram‑positive bacteria. Antibiotic resistant bacteria are found in all living hosts and in the environment and move between hosts and ecosystems. An intricate interplay of infections, exposure to antibiotics, and disinfectants at individual and community levels among humans, animals, bir… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Among the remaining 20 articles that employed intrinsic relationships between One Health and fish, eight were reviews rather than primary ones. Consequently, 12 final articles met all the criteria pre-established by this systematic review (Figure-1 and Table -3) [12][13][14][15][16][17][18][19][20][21][22][23].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the remaining 20 articles that employed intrinsic relationships between One Health and fish, eight were reviews rather than primary ones. Consequently, 12 final articles met all the criteria pre-established by this systematic review (Figure-1 and Table -3) [12][13][14][15][16][17][18][19][20][21][22][23].…”
Section: Resultsmentioning
confidence: 99%
“…Alhaji et al 2021 [12] Nigeria, West Africa Food control Scopus Brunton et al 2019 [13] Vietnam, Southeast Asia Science of the total environment Scopus Sapugahawatte et al 2022 [14] Hong Kong, China Antibiotics PubMed Das et al 2020 [15] Khorda, India JMIR research protocols Scopus Cerdeira et al 2020 [16] Belém, Brazil Genomics Scopus Minja et al 2021 [17] Tanzânia, East Africa Antibiotics Scopus Sapugahawatte et al 2020 [18] Hong Kong, China mSphere PubMed Pace et al 2020 [19] Naples [23] Uganda, East Africa Cogent Food and agriculture PubMed identify emergency hotshots of antibiotic-resistant bacteria attributed to human exposure. Thus, the results revealed that the growth stage of individuals is crucial for the emergence of highly resistant bacteria due to the exacerbated use of antimicrobials and the consequent exposure to contaminated water.…”
Section: Author Year Place Of Publication Journal Databasementioning
confidence: 99%
“…Increased drug resistance of bacteria could be effectively avoided through targeted therapy [ 28 , 29 , 30 ]. At the same time, the evolution and spread of bacterial drug resistance could be reduced [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…13 In addition, CBS is one of the few suitable options for supporting OneHealth surveillance activities given its proximity to the interface between humans and animals. 14 15 Given its potential to enhance the early warning and containment function of national surveillance systems, CBS is increasingly framed as a promising surveillance modality in the discourse around global health security. 16 …”
Section: Introductionmentioning
confidence: 99%
“…A CBS system can: provide early case detection and reporting during disease outbreaks; monitor events of public health importance in humanitarian emergencies; and supplement non-existent or limited surveillance coverage in other complex settings 13. In addition, CBS is one of the few suitable options for supporting OneHealth surveillance activities given its proximity to the interface between humans and animals 14 15. Given its potential to enhance the early warning and containment function of national surveillance systems, CBS is increasingly framed as a promising surveillance modality in the discourse around global health security 16…”
Section: Introductionmentioning
confidence: 99%